Fat embolism and COVID-19 infection: autopsy and post-mortem laboratory findings in SARS-CoV-2 positive patients - Adriana Gavronova; Lukas Hamerlik; Margita Bartkova; Vaclav Svrchokryl; Veronika Kralikova; Katerina Vranova; Peter Ondra; Martin Dobias (Biomedical Papers)
Introduction. The article is one of the very first autopsy reports worldwide, which associates COVID-19 infection and pulmonary fat embolism. Aims. To point to a crucial connection between a severe acute respiratory syndrome caused by coronavirus 2 (SARS-CoV-2) infection and pulmonary fat embolism as one of the possible major mechanisms of severe COVID-19 symptoms. Methods. Lung, brain and kidney tissues examination of 16 full human autopsy cases. All deceased suffered from COVID-19 infection, none of them was admitted to hospital prior to death, immediate causes of death vary. Autopsies accompanied by microbiological examination and histological examination using Oil Red O staining were performed. Consequently, we have implemented a control cohort consisting of 16 deceased with no presence of pulmonary infection and various immediate causes of death. Results. Of the 16 autopsy cases, 11 (68.8%) were males and 5 (31.3%) females, with overall mean age 68.1 (39-86) years. Causes of death of studied subjects were natural, mostly from respiratory failure (in 12 cases, 75%). Cardiopulmonary resuscitation was performed in 7 cases (43.8%). None of dissected persons had larger signs of body trauma. Pulmonary fat embolism was found in 11 cases (68.8%), which generalised to kidneys in 8 patients (50% of all cases, 72.3% of cases with pulmonary fat embolism) and to brain tissue in 1 case. Conclusion. We demonstrated a reasonable relation between a COVID-19 disease and a variously severe fat embolism, severity of which does not directly correlate with body weight. Further investigation or even change of medical treatment needs to be considered in patients with COVID-19.